Communication and navigation integration for LEO constellations:status, opportunities, and challenges - Yafei ZHAO; Bing YAN; Yaohua SUN; Mugen PENG (Dianxin kexue)
With the growing maturity of millimeter wave technology and high-throughput satellite communication technology, as well as the urgent need for global broadband communication services, the construction of LEO giant communication constellation has attracted great attention, and up to thousands of satellites have been deployed.A large number of LEO communication satellites have realized multiple and repeated coverage of high-frequency radio frequency signals on the ground.At the same time, ground communication resources provide a hardware platform for signal reception and create conditions for the development of integrated communication and navigation.The status quo, opportunities and challenges of the integrated LEO navigation constellation were discussed, and the differences of resources required by the integrated LEO navigation constellation and the global navigation satellite system were emphatically expounded.In terms of space segment, ground segment and user segment, the conclusions and prospects for future research were presented.